Status of local knowledge and information literacy among The Minangkabau Community in Indonesia - Rahmah, Elva; Mohamed Shuhidan, Shamila; Wan Yahaya, Wan Aida (Record and Library Journal, 2024)
Background of the study: The topics of local knowledge and information literacy have tremendously been discussed in research on information literacy and local knowledge around the world, including in Indonesia. However, these aspects are still under-researched particularly when it comes to the issue of the status local knowledge and that is related to information literacy. Based on this main gap, this paper presents a study that examined local knowledge and information literacy, to specifically address the issue. Purpose: To identify the status of local knowledge and information literacy among the Minangkabau Community in Agam district, Indonesia. Method: A quantitative approach by using a survey was conducted involving 384 Minangkabau communities in Agam district, Indonesia selected using a random sampling technique Findings: The findings reveal a significant value of 0.000 (p0.05), indicating that there is a substantial positive link between tacit and explicit knowledge and information literacy. Furthermore, the Pearson correlation coefficient value shows a value of 0.712 which is in the range of 0.60 – 0.799 so it is in a strong category. From the results, the analysis shows that the Minangkabau community has positive information literacy and the local knowledge processes variable can encourage activities of local knowledge in the community, special in Agam district, Indonesia.  Conclusion: Status of local knowledge cover combination of knowledge such as from tacit and explicit will support the Minangkabau community to sustain their local knowledge with accurate information seeking strategies